A Novel Approach for Safeguarding Kurdish Text Files via Modified AES-OTP and Enhanced RSA Cryptosystem on Unreliable Networks - Newroz Nooralddin Abdulrazaq (Eurasian Journal of Science and Engineering)
In line with the growth of the e-governate, the Kurdistan Regional Government is actively adopting digital transformation, which underscores the urgent requirement for distinct encryption methods that are practical for the Kurdish alphabet in the fields of administration and digital governance. This paper provides a new method for encrypting and decrypting classified text files in the Kurdish alphabet using the modified Advanced Encryption Standard (AES) cipher system with the adoption of Cipher Block Chaining (CBC) mode based on a one-time pad (OTP) cipher. The provided work also uses the modified RSA cipher system to transmit randomly generated secret keys for both AES and OTP via untrustworthy channels. The modified RSA cipher system is based on randomly selecting two large co-prime numbers under the restriction, each having at most two factors, instead of two large prime numbers.